Herbert Marcuse Today: On Ecological Destruction, Neofascism, White Supremacy, Hate Speech, Racist Police Killings, and the Radical Goals of Socialism. (December 2021) - Reitz, Charles
Herbert Marcuse's political-philosophical vision, cultural critique, and social activism continue to offer an intelligent strategic perspective on current concerns – especially issues of ecological destruction, neofascist white supremacy, hate speech, hate crimes, and racist police violence. These can be countered through a recognition of the intersectionality of radical needs of diverse constituencies and radical collaboration, giving rise to system negation as a new general interest, and an ecosocialist strategy of revolutionary activism within a global alliance of transformational forces.